Isolasi dan Karakterisasi Kapang Filoplan serta Serasah Daun di Lingkungan Laboratorium Biologi Universitas Diponegoro Dengan Metode Contact Plate - Mahardika, Wahyu Aji; Dion, Romario; Qoys Naufal, Mochammad Fa’iq; Ramadhany, Warih; Lunggani, Arina Tri (Bioma : Berkala Ilmiah Biologi, 2021)
Fungi can be present on various substrates in the surrounding environment. The presence of these molds takes advantage of the nutrients that are attached to or contained in the substrate. The purpose of this study was to isolate and obtain various types of molds from various substrates. The method used in this study is a contact plate by attaching it to various objects or substrates, namely leaf litter, composter walls, tables, glass, and cabinets. The fungi obtained were 6 isolates, including those from the genus Aspergillus, Penicillium, Curvularia, and Alternaria,